Adaptation Strategies for Indonesian Islamic Higher Education Facing the Industrial Revolution Big Data and Omics Era - M. Mukhsin Jamil; Helmiati; Khusna Amal (JURNAL PENELITIAN, 2025)
The advent of Industrial Revolution 4.0 and 5.0 has precipitated substantial changes across myriad fields, including higher education. These developments have been particularly pronounced in America, Europe, the United Kingdom, China, and Asia. Islamic universities, in particular, confront distinctive challenges in adapting to technological advancements such as Big Data and Omics (in the health sector) following the emergence of the novel Coronavirus, while concurrently upholding Islamic principles within the educational curriculum. This article aims to examine adaptation strategies that can be implemented by Indonesian Islamic universities in facing this digital transformation era. Using a literature review approach and conceptual analysis, this article explores the integration of Big Data technology to support data-based decision-making, the development of Omics-based research in biotechnology and health, and curriculum development efforts that combine technology and Islamic values. The results of this study demonstrate that the successful adaptation of Islamic higher education in Indonesia is contingent upon the enhancement of collaboration between academia, industry, and the community, the improvement of digital literacy among faculty and students, and the promotion of policies that demonstrate responsiveness to technological developments. In conclusion, Islamic higher education should aspire to a proactive role in the integration of modern technology with Islamic values, with the objective of creating a more relevant and internationally competitive educational ecosystem.